Ta grade 3/high grade non‐invasive bladder cancer: Should we perform a second TUR?. Issue 4 (28th December 2020) - Tinay, Ilker; Baltaci, Sumer; Demirdag, Cetin; Akdogan, Bulent; Yucetas, Ugur; Simsekoglu, Muhammed Fatih; Haberal, Hakan Bahadır; Bozlu, Murat; Izol, Volkan; Aslan, Guven; Bekiroğlu, Nural; ,
Abstract: Purpose: To evaluate the effect of second transurethral resection (TUR) on oncological outcomes, according to the presence or absence of detrusor muscle in the initial TUR of patients with pTa Grade 3/high grade (G3/HG) tumours, who received at least 1 year of maintenance Bacillus Calmette‐Guerin (BCG) therapy. Patients and methods: In this retrospective study, we evaluated the effect of second TUR on oncological outcomes of 93 patients with pTa G3/HG tumours, according to the presence or absence of muscle in the initial TUR. All patients received maintenance BCG therapy according to the SWOG protocol. Results: Median follow‐up was 36 months. If muscle is present in the initial TUR, a second TUR significantly increased median time to first recurrence, compared to those without a second TUR (77.6 vs 36.9 mos, P  = .0086). If muscle is missing in the initial TUR, a second TUR significantly decreased recurrence rate (20% vs 66.7%, P  = .002), increased median time to first recurrence (78.9 vs 42.7 mos, P  = .0001) and median time to progression (22 vs 7 mos, P  = .05), compared to those without a second TUR. Conclusion: In patients with pTa G3/HG tumours, if the muscle is missing in the initial TUR, a second TUR should be performed in order to attain lower recurrence rates and longer median time to recurrence and progression. If the muscle is present in the initial TUR, a second TUR will only increase median time to first recurrence.